International Office Professionals: An Example of Street-Level Bureaucrats in Higher Education - Betul Bulut-Sahin (MDPI AG, 2023)
Internationalization has become an indispensable part of universities worldwide. Since the 1990s, various research has been conducted with those often seen as the main stakeholders of universities, namely administrators, academics, and students. However, the leading implementors of internationalization and especially mobility programs, international office professionals (IPs), are rarely considered by research. In this study, qualitative research was conducted through 36 semi-structured interviews with IPs in Poland and Turkey. The results revealed that IPs have several professional and institutional challenges. While the professional challenges include diversified responsibilities, incoming students' problems, and communication difficulties with the young generation; institutional challenges are mainly associated with administrative issues like lack of participation in decision-making, temporarily appointed leaders, and lack of academic support. Additionally, in this study, IPs were referred to as street-level bureaucrats as the main contact with the beneficiaries of internationalization. The research revealed that IPs use a high level of discretion in practice. This paper presents examples of how to structure internationalization policies so that the IPs use their power of discretion in a positive way, contributing to policy implementation. Therefore, this paper aims to provide a roadmap for the practical implementation of internationalization and mobility programs in universities.